Fishbowl Technique towards the Students’ Speaking Skill - Anakotta, Raisa; Nursalim, Nursalim; Latuheru, Reka Judahida (INTERACTION: Jurnal Pendidikan Bahasa, 2020)
The objective of this research is to describe whether or not fishbowl technique can improve students’ speaking of tenth grade of IPS 1 in SMA N 2 Sorong Regency. In this study, the researcher conducted the quantitative research using the method pre-experimental design type of the one group pre-test. Therefore, the researcher took 30 students as the sample from the population. The researcher used SPSS Analysis Version 20.0, the researcher gave the interpretation towards “t” score by comparing t-value with t-table. The researcher interpretation that t-value is 3.048 with the significance value is 0.05. The score of t-table is 2.045 with the significance level of 0.05 with df 29. P-value is 0.0005 < 0.05, it is known that t-value > t-table ( 3.048 > 2.045 ). Meanwhile, the alternative (H1) is accepted and null hypothesis (Ho) is rejected. It means that using fishbowl technique can improve students speaking skill at the tenth of SMAN 2 Sorong Regency. But this technique is not effective towards students’ speaking skill, because it is not achieve score of KKM that is > 68.